If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10 + z = -9z Solving -10 + z = -9z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '9z' to each side of the equation. -10 + z + 9z = -9z + 9z Combine like terms: z + 9z = 10z -10 + 10z = -9z + 9z Combine like terms: -9z + 9z = 0 -10 + 10z = 0 Add '10' to each side of the equation. -10 + 10 + 10z = 0 + 10 Combine like terms: -10 + 10 = 0 0 + 10z = 0 + 10 10z = 0 + 10 Combine like terms: 0 + 10 = 10 10z = 10 Divide each side by '10'. z = 1 Simplifying z = 1
| 5x+5-3x+3=7x+3-x+6 | | 2n-16=-16 | | 21k^2-35k-8=-8 | | 7t-10=-16+8t | | ln(5x-2)-ln(3x-2)=ln(15x-6)-ln(5x+2) | | x+5x+6=29 | | 3(3S+1)=111 | | 8y+x=20 | | 3n^2-39n=-120 | | 3w-w=16 | | f(x)=-16x^2+96x+12 | | -5(x-6)=85 | | 4+10=22 | | r^2+7r+5=-7 | | 3(S+1)=36 | | 0=2x^2-32 | | -9w+8w+2=-3 | | 26m=650 | | 6(v-5)(5v+8)=0 | | 4(2L+1)=111 | | -11-n=-11 | | 3x+(x+38)=90 | | 14=5+h | | U-1=-4 | | -46=p-19 | | 8a-4-3a=12 | | 13-4x=-x-31 | | (x+54)+2x=90 | | 8x-4=-1 | | (x+54)+2x=180 | | 6(3x+5)=100 | | 6x+7c=37cforx |